CARICOM Single Market and Economy : genesis and prognosis - Hall, Kenneth (Ian Randle KingstonJM, 2007)
Focuses on the genesis of the CSME and progress achieved towards its full implementation. Deals with important dimensions of the actual evolutionary process. Looks at where we have come from and gives visions of where we appear to be heading.